THE EFFECTIVENESS OF THE DRAMA METHOD ON LEARNING MOTIVATION IN HISTORY SUBJECT CLASS XI STUDENTS SMA 1 GAMPING FOR ACADEMIC YEAR 2021/2022 - Ernawati (CV. Fahr Publishing, 2023)
This study aims to: (1) Test the effectiveness of using the drama method on students' history learning motivation (2) Testing the effectiveness of using conventional methods on students' history learning motivation (3) Testing which learning method is more effective with the use of drama methods than conventional methods on learning motivation. student history. This study uses a quantitative approach with a quasi-experimental research design (Randomized Control Group Pretest-Posttest Design). The research population was all students of class XI IPS SMA 1 Gamping. Sampling using sampling technique. The research instrument includes an observation sheet on the implementation of learning and a questionnaire sheet for pretest-posttest results of students' learning motivation. Hypothesis testing of posttest data with IBM SPSS 28 software. The effectiveness hypothesis test used one sample t-test analysis and two independent mean difference t-tests to determine which learning was more effective. The results of the study: (1) Learning with drama method is effective on students' learning motivation as evidenced by the value at (P-value = 0.450 > 1/2α = 0.025). (2) Learning with conventional methods is effectively applied in the learning process to the motivation to learn history of class XI SMA Negeri 1 Gamping seen at (P-value = 0.495 > 1/2α = 0.025). (3) Learning with the drama method is more effectively applied than conventional methods in the learning process on the motivation to learn history of class XI students of SMA Negeri 1 Gamping seen with the value (P-value = 0.009 < = 0.05).